THU0262 Sclerostin does not predict radiographic progression in patients on anti-tnf therapy – new results from the european ankylosing spondylitis (AS) infliximab cohort (EASIC). (23rd January 2014) - Baraliakos, X.; Heldmann, F.; Listing, J.; Schett, G.; Appelboom, T.; Brandt, J.; van den Bosch, F.; Breban, M.; Burmester, G.; Dougados, M.; Emery, P.; Gaston, H.; et al.
Abstract : Background: Anti-TNF therapy has been shown to be clinically efficacious in patients with ankylosing spondylitis (AS) but there is no evidence that it inhibits new bone formation. Biomarkers of increased bone turnover such as bone alkaline phosphatase (BAP) and sclerostin, an inhibitor of bone formation of the Wnt pathway, may play a role in new bone formation known to occur in AS. Objectives: Taking advantage of the patient data accumulated in the European cohort EASIC we studied the influence of serum levels of SCL and BAP and prevalent syndesmophytes on the development of syndesmophytes over 2-5 years (y) in patients treated with infliximab and other anti-TNF agents. Methods: All patients participating in EASIC with complete data sets of sera and conventional radiographs of the cervical and lumbar spine at baseline (BL), 2y and 5y, were included in the study. BAP and sclerostin were measured by ELISA, as recently described. The results were correlated to proposed cut-offs for radiographic progression: slow = ≤1 syndesmophyte (synd) within 2y, moderate = ≤2 synd/2y, and fast = >2 synd/2y). Radiographs were read blinded to time sequence by one experienced reader. Analysis of variance based on rank transformed data (van der Waerden scores) were used to compare the patient groups. Results: Overall, 50/70 patients had syndesmophytes at BL. New syndesmophytes developed in 27 (38.6%) and 35 (50%) patients after 2y and 5y, respectively. Overall, 0/27 and 16/35 (45.7%) patients showed slow, 27/27 (100%) and 12/35 (34.3%) moderate and 0/27 and 1/35 (2.9%) fast radiographic progression after 2y and 5y, respectively. Patients with BL-syndesmophytes tended to have more rapid radiographic progression. Sclerostin levels at BL were significantly lower in patients with syndesmophytes at BL (0.8±0.3 pg/ml), than in those without (1.1±0.5 pg/ml), p=0.009. There was no significant difference in BL-sclerostin levels in the 3 groups with different velocity of radiographic progression after 2y and 5y. There was no correlation of BAP at BL on radiographic progression after 2 and 5y. Conclusions: In contrast to an earlier study we found no predictive value of sclerostin levels for new bone formation in AS in this trial with anti-TNF treated patients. Whether this is due to the anti-TNF treatment remains unclear at present. However, sclerostin levels did correlate with radiographic damage at BL, but they did not differentiate between different types of progression. Presence of ≥1 syndesmophyte at BL is the strongest predictor of radiographic progression, also after 5y of follow up. However, there was only 1 fast progressor in our study. Disclosure of Interest: None Declared